Challenges and strategies for improving lecturer research performance through research-oriented key performance indikator 7 at Universitas Nurtanio Bandung - Edah Jubaedah; Raya Mustiraya; Sri Sutjiningtyas; Hendrik Sudria Munawar (Rafandha Press, 2026)
Background: Research performance is a key indicator of institutional quality and academic competitiveness in higher education. Universitas Nurtanio Bandung faces challenges in optimizing KPI 7 achievement, particularly in lecturer research productivity, scientific publications, external grants, intellectual property outputs, and institutional reward mechanisms. Purpose: This study aims to analyze the current condition of KPI 7 achievement and formulate optimization strategies to improve lecturer research performance at Universitas Nurtanio Bandung. Method: This study used a qualitative approach with a descriptive exploratory design. Data were collected through in-depth interviews with nine structural leaders, including vice rectors, research institution leaders, and faculty deans. The data were transcribed and analyzed using NVivo 12 through word frequency analysis, text search query, coding analysis, hierarchy chart, and project map visualization. Findings: The findings show that lecturer research activities are dominated by internal and external grant-based schemes. The main obstacles include limited external research grants, low journal publication productivity, insignificant intellectual property outputs, competition among lecturers, and the absence of a structured reward system. The study indicates that KPI 7 optimization requires an integrated strategy through stronger institutional policy, lecturer capacity building, research mentoring, external collaboration, grant access expansion, publication support, and a clear reward system. These findings highlight the importance of institutional commitment in building a sustainable research culture and improving lecturer research performance.